(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2016)
In the article the special features of women’s characters are analyzed using Hanna Barvinok’s stories as examples. The main attention is concentrated on mental traits of Ukrainian women, who are considered as possessors of moral, ethical, Christian and family values of Ukrainian people.